Marketing Mix, Market Competition and Quality of Service in South Sulawesi - Handojo Wibawanto Soetikno; Carunia Mulya Firdausy; Haris Maupa; Syarifuddin Sulaiman (Proceeding of The International Conference on Business and Economics, 2023)
Minimarket development today has increased dramatically, the increase was driven by consumer behavior which makes shopping as a necessity to meet their daily survival. This study aims to analyze (1) the marketing mix, market competition and quality of service for the mini choice for shopping. (2) the dominant influence of the marketing mix as a mini-shopping options. This research is quantitative descriptive study using observational approach. Data collection techniques used include interviews, observation, study documentation, and questionnaires. The population in this study are all consumers minimarket (Alfamidi, Indomart and k-circle) in South Sulawesi. The sampling method used is proportional stratified purposive sampling. In analyzing the data in this study used multiple linear regression analysis technical. The results showed that the variables of the marketing mix, market competition and quality of service simultaneously strong and positive impact on the choice of minimarket in South Sulawesi. These results prove the first hypothesis testing. Partial test, it was found that the marketing mix variables dominating influence minimarket choice, it is asserted that the second hypothesis can be accepted. All independent variables (the marketing mix, market competition, and quality of service) has an influence on the mini choice of 42.6%, while the remaining 57.4% is explained by causes (variables) other than this study.